2013
DOI: 10.1149/2.021309jss
|View full text |Cite
|
Sign up to set email alerts
|

Penetration of Copper-Manganese Self-Forming Barrier into SiO2Pore-Sealed SiCOH during Deposition

Abstract: The incorporation of a self-forming Cu diffusion barrier on pore-sealed SiCOH was investigated. SiCOH films 20% porous and 230 nm thick were capped with 36 nm SiO2. Fabricated structures (Cu-Mn/SiO2/SiCOH) were subjected to a back-side Secondary Ion Mass Spectrometry (SIMS) depth profile study to assess the extent of metal migration. SIMS depth profiles revealed that Cu and Mn diffused in significant amounts across the SiO2 layer during fabrication steps. A mass transport model was used to describe the migrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…10 Recent studies have shown that the formation of Mn silicate barriers on carbon doped low-κ dielectrics can result in the removal of carbon from the dielectric, 11 while the use of porous low-κ materials can result in the integration of gaseous Mn precursors within the dielectric pore structure. 12 As such, investigating the formation of Mn based self-forming barrier layers on SiO 2 in this paper is intended to act as an important base line study before investigating the more complex Mn/SiOC:H interface. To date, the characterization of the structural and chemical nature of the self-formed diffusion barrier layers using transmission electron microscopy (TEM) and related analytical techniques has been carried out mainly in conventional TEM and high resolution TEM modes after the barrier formation process is complete.…”
mentioning
confidence: 99%
“…10 Recent studies have shown that the formation of Mn silicate barriers on carbon doped low-κ dielectrics can result in the removal of carbon from the dielectric, 11 while the use of porous low-κ materials can result in the integration of gaseous Mn precursors within the dielectric pore structure. 12 As such, investigating the formation of Mn based self-forming barrier layers on SiO 2 in this paper is intended to act as an important base line study before investigating the more complex Mn/SiOC:H interface. To date, the characterization of the structural and chemical nature of the self-formed diffusion barrier layers using transmission electron microscopy (TEM) and related analytical techniques has been carried out mainly in conventional TEM and high resolution TEM modes after the barrier formation process is complete.…”
mentioning
confidence: 99%
“…43 The decay constant, s, results from the interplay between carrier scattering and trapping events. 43 Expressions (1) (14). Our model is able to predict the curvature of the current decay more accurately than the empirical, stretched exponential fit due to its ability to describe the evolution of s. In essence, s describes the way charge carriers interact with defects and varies as the number of defects changes overtime.…”
Section: Resultsmentioning
confidence: 99%
“…The model presented in Eqs. (1)- (14) describes how changes in the material brought forward by the transport of mobile defects can potentially affect the shape and curvature of the long-tail decay.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations